2023
DOI: 10.1155/2023/4007616
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Treatment in Women with Stage I Endometrial Cancer: A Retrospective Study

Abstract: Objective. To evaluate whether postoperative adjuvant treatment is beneficial for patient survival after surgery for early stage endometrial cancer (EC). We analyzed the outcomes of patients treated with radiotherapy, chemotherapy, or progestagen combined with other adjuvant treatments. Methods. We analyzed the outcomes of patients treated with radiotherapy alone, chemotherapy alone, or progestagen treatment with other adjuvant treatments. Women without any adjuvant treatment after operation were used as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Lymph node involvement was present in 17.48% of women with endometrial cancer. The median (IQR) number of lymph nodes collected during surgery was 16 (12)(13)(14)(15)(16)(17)(18)(19)(20) for pelvic and 4 (3-5) for paraaortic nodes. The mean CA-125 level for patients was 28.8±33.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node involvement was present in 17.48% of women with endometrial cancer. The median (IQR) number of lymph nodes collected during surgery was 16 (12)(13)(14)(15)(16)(17)(18)(19)(20) for pelvic and 4 (3-5) for paraaortic nodes. The mean CA-125 level for patients was 28.8±33.0.…”
Section: Resultsmentioning
confidence: 99%
“…15 On the other hand, in a study encompassing risk factors affecting overall survival and disease-free survival in early-stage endometrial cancer, it was found that CA-125 had no significant effect on overall survival and disease-free survival. 16 The accurate staging of endometrial cancer relies on well-established and evidence-based surgical staging protocols. Clinical staging alone lacks precision and cannot evaluate critical factors such as LVSI, grade, or A cutoff value of >35 was determined for the advanced stage with 96% sensitivity and 92.4% specificity according to the ROC Curve analysis in our study.…”
Section: Resultsmentioning
confidence: 99%